Do the students of Kalmykia need Kalmyk language (according to sociological surveys of 2015 and 2017) - Namrueva, Lyudmila V. (The New Research of Tuva, 2018)
One of the languages in Russia under the certain degree of danger of vanishing is Kalmyk language – a mother tongue for dominant ethnic group of the Republic of Kalmykia. Sociological surveys reveal that it is being spoken by less and less number of people. The language is shifting from the ethnodifferentiating feature to the symbolic attribute of an ethnos. Kalmyk language is occupied rarely as a mean of communication among youth, especially out of home (at work, school or public). Article presents the results of survey and juxtaposition of answers of Kalmyk youth and Kalmyk and Russian students. Article fixes the low level of communication on Kalmyk language among youth. Only 43% of respondents were bilingual (speaking both Russian and Kalmyk) in 2015 and 46% - in 2017. Main reason for this is absence of Kalmyk language verbal environment rather than non-ability to speak the language. Demand for learning the national language of the republic exists: only 4% of students polled said they don’t need to learn Kalmyk language, while 52.5% would select standard, 20% - extended, 18% - shallow level of learning Kalmyk language. In 2017 level of this demand significantly degraded and author sees reason for this in change of institutions in survey. Explicit high demand among the students is learning foreign languages (English at first place). Significant less demand is for traditional courses of the history of region, history of ethnos and national culture. Nevertheless, youth are interested in exposure of national cultures but in form of practical learning in theaters, concerts or tourist treks rather than formal educational practices.